2020
DOI: 10.1016/j.celrep.2020.107837
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Human ATG9A, the Only Transmembrane Protein of the Core Autophagy Machinery

Abstract: Highlights d The transmembrane autophagy protein ATG9A is a domainswapped homotrimer d Each ATG9A protomer comprises four transmembrane domains d The ATG9A homotrimer exhibits an internal network of branched cavities d Molecular dynamics simulations show that ATG9A trimers deform membranes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
141
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(150 citation statements)
references
References 39 publications
8
141
1
Order By: Relevance
“…In contrast, a recent study showed that Optineurin can directly associate with ATG9A to induce mitophagy without the engagement of FIP200 56 . To validate the direct interaction between Optineurin and ATG9A, we constructed an ATG9A(595-839) fragment that includes the entire C-terminal cytosolic tail of ATG9A based on the recently determined human ATG9A structure 57,58 . Using purified ATG9A(595-839) and full-length Optineurin proteins, our biochemical assays clearly demonstrated that there is no direct interaction between the cytosolic tail of ATG9A and Optineurin in vitro ( Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a recent study showed that Optineurin can directly associate with ATG9A to induce mitophagy without the engagement of FIP200 56 . To validate the direct interaction between Optineurin and ATG9A, we constructed an ATG9A(595-839) fragment that includes the entire C-terminal cytosolic tail of ATG9A based on the recently determined human ATG9A structure 57,58 . Using purified ATG9A(595-839) and full-length Optineurin proteins, our biochemical assays clearly demonstrated that there is no direct interaction between the cytosolic tail of ATG9A and Optineurin in vitro ( Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Current evidence supports a role for AP-4 in promoting autophagosome biogenesis through regulation of autophagy-related protein 9 (ATG9) export from the trans-golgi network to autophagosomes [ 15 , 19 , 20 , 21 ]. ATG9 is the only transmembrane protein of the core autophagy machinery, and its distribution is heavily dependent on vesicular trafficking [ 71 , 72 , 73 ]. Consequently, loss of AP-4 function leads to retention of ATG9 in the trans-golgi network and defective autophagosome generation [ 15 ].…”
Section: Ap-4 Complexmentioning
confidence: 99%
“…In addition, recent studies have highlighted that TRAPP III-specific proteins (TRAPPC11) are necessary for the close of isolation membranes and recruitment of WIPI4-ATG2 to isolation membranes with the presence of ATG9, perhaps due to its carboxy-terminus, while TRAPPC12 is downstream of TRAPPC11 ( Stanga et al, 2019 ). Interestingly, Guardia et al (2020) have found that ATG9A (human ATG9), a homotrimer with four transmembrane helices, interacts with ATG2 at C-terminal platform domain of ATG9A (1–723 construct and 1-522 construct) to transfer lipids from ATG2 to ATG9A, and then ATG9A can induce the autophagosome membrane curvature for the further processes of autophagy.…”
Section: Overview Of Autophagymentioning
confidence: 99%